2006
DOI: 10.2478/s11535-006-0009-3
|View full text |Cite
|
Sign up to set email alerts
|

Extra-cellular chromate-reducing activity of the yeast cultures

Abstract: This paper reports on the experimental data supporting an essential role of extracellular reduction in chromate detoxification by baker's and non-conventional yeasts. A decrease of chromate content in the yeast culture coincides with an increase of Cr(III) content in extracellular liquid. At these conditions, cell-bound chromium level was insignificant and a dominant part of extra-cellular Cr(III) species was detected in the reaction with chromazurol S only after mineralization of the cell-free samples. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…The Cr(VI) is actively transported through the biological membrane of prokaryotic and eukaryotic microorganisms (Alluri et al 2007), and once inside the cell, Cr(VI) is reduced to Cr(III), most likely through the formation of instable intermediary forms of Cr(V) and Cr(IV) by nonenzymatic (indirect) or enzymatic reactions (direct) (Ksheminska et al 2006); the latter is still uncertain for eukaryotic microorganisms (Gadd 2010).…”
Section: Cr(vi) Biotransformation (Reduction)mentioning
confidence: 99%
See 1 more Smart Citation
“…The Cr(VI) is actively transported through the biological membrane of prokaryotic and eukaryotic microorganisms (Alluri et al 2007), and once inside the cell, Cr(VI) is reduced to Cr(III), most likely through the formation of instable intermediary forms of Cr(V) and Cr(IV) by nonenzymatic (indirect) or enzymatic reactions (direct) (Ksheminska et al 2006); the latter is still uncertain for eukaryotic microorganisms (Gadd 2010).…”
Section: Cr(vi) Biotransformation (Reduction)mentioning
confidence: 99%
“…For eukaryotic cells, knowledge regarding enzymes for chromate reduction remains very limited (Ksheminska et al 2006). In bacteria, the existence of ChrA proteins as part of a chromate transporter (CHR) superfamily has been informed and is related to the transport of sulphate and chromate (Nies et al 1998).…”
Section: Direct Reductionmentioning
confidence: 99%
“…However, for the chromate-resistant strains of Candida maltosa a NAD-dependent chromate reducing activity was observed [14]. Recently we have found that some reducing substances, secreted extracellularly by yeast played a significant role in Cr(VI)-detoxification [10,11]. As a product of chromate reduction, trivalent Cr(III) formed complexes with some specific components of culture liquid which were not adsorbed by the cells.…”
Section: The Main Pathway Of Cr(vi) (Hexavalent Chromium) Detoxificatmentioning
confidence: 99%
“…Taking into account significant kinetic inertness of chromium(III) salts in the formation of even thermodynamically stable complexes, it is promising to produce such complexes by using microbial cells capable of reducing chromium(VI) (chromate, dichromate) to Cr(III)-biocomplexes (Puzon et al 2005;Ksheminska et al 2006Ksheminska et al , 2008. Although the genetic and biochemical aspects of this process have been insufficiently studied, it is known that chromate anions are transported into the cells through sulfatespecific permease(s) coded, in the case of baker's yeast, by the genes SUL1 and SUL2 (Cherest et al 1997) and can be reduced, as a powerful oxidative agent, to Cr(III) by cellular reducing systems which can include enzymatic and non-enzymatic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial reduction of chromate is well-established. It runs through the different enzymatic pathways which function under aerobic and anaerobic conditions with the use of hydrogenase, cytochrome cdependent electron transfer chains, nitrate reductase, flavin reductase, ferrireductase, some flavoproteins, and NADH and NAD(P)H-dependent reductases (Ksheminska et al 2006). For eukaryotic microbial cells and, primarily, yeasts, the data on the chromatereducing systems are more ambiguous.…”
Section: Introductionmentioning
confidence: 99%